2014
DOI: 10.1038/srep07564
|View full text |Cite|
|
Sign up to set email alerts
|

G Protein-coupled Estrogen Receptor Protects from Atherosclerosis

Abstract: Coronary atherosclerosis and myocardial infarction in postmenopausal women have been linked to inflammation and reduced nitric oxide (NO) formation. Natural estrogen exerts protective effects on both processes, yet also displays uterotrophic activity. Here, we used genetic and pharmacologic approaches to investigate the role of the G protein-coupled estrogen receptor (GPER) in atherosclerosis. In ovary-intact mice, deletion of gper increased atherosclerosis progression, total and LDL cholesterol levels and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
155
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 56 publications
(135 reference statements)
14
155
2
2
Order By: Relevance
“…Despite conflicting results obtained with the different mice models of GPER inactivation,52 GPER activation has been reported to exert several beneficial effects in the cardiovascular system, including protection against atherosclerosis and hypertension 53, 54. Treatment with the selective agonist G‐1 reduces atherosclerosis in ovariectomized mice, and the beneficial effects of GPER in this model are associated with a reduction in macrophage and T‐cell recruitment, indicating an anti‐inflammatory mechanism 55. In addition, activation of GPER has been reported to protect female mice from salt‐ and pressure‐induced vascular damage 56, 57.…”
Section: Discussionmentioning
confidence: 94%
“…Despite conflicting results obtained with the different mice models of GPER inactivation,52 GPER activation has been reported to exert several beneficial effects in the cardiovascular system, including protection against atherosclerosis and hypertension 53, 54. Treatment with the selective agonist G‐1 reduces atherosclerosis in ovariectomized mice, and the beneficial effects of GPER in this model are associated with a reduction in macrophage and T‐cell recruitment, indicating an anti‐inflammatory mechanism 55. In addition, activation of GPER has been reported to protect female mice from salt‐ and pressure‐induced vascular damage 56, 57.…”
Section: Discussionmentioning
confidence: 94%
“…GPER has now been established to play an important role in vascular endothelial function because it induces vasodilation and inhibits vascular smooth muscle proliferation [38]. GPER activation also stimulates human endothelial nitric oxide synthase [38,39]. Most recently, Meyer at al [39] showed that chronic treatment with G-1, a synthetic, highly selective small molecule agonist of GPER, reduced postmenopausal atherosclerosis and inflammation without uterotrophi effects.…”
Section: Role Of G Protein-coupled Estrogen Receptor In Normal Vasculmentioning
confidence: 97%
“…Most recently, Meyer at al [39] showed that chronic treatment with G-1, a synthetic, highly selective small molecule agonist of GPER, reduced postmenopausal atherosclerosis and inflammation without uterotrophi effects. This study establishes the atheroprotective function of GPER and introduces selective GPER activation as a novel therapeutic approach to inhibit post-menopausal atherosclerosis and inflammation in the absence of uterotrophic activity [39].…”
Section: Role Of G Protein-coupled Estrogen Receptor In Normal Vasculmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent reports have also demonstrated that specifically GPER expression, but not that of ERa or ERb, is required for the protective effects of E2 on myocardial reperfusion injury (Bopassa et al, 2011(Bopassa et al, , 2012a. Finally, GPER knockout mice also show increased atherosclerosis and vascular inflammation when fed a high-fat atherogenic diet, with G-1 treatment of wild-type mice reducing both plaque formation and macrophage infiltration (Meyer et al, 2014).…”
mentioning
confidence: 96%